STUDY OF AWARENESS ABOUT CERVICAL CANCER, HPV INFECTION AND HPV VACCINE AMONG MEDICAL STUDENTS - P.M Durgawale, Supriya.S. Patil, S.R Patil, Aparna.V.S, Viyusha. T. Viswanathan (International Journal of Advanced Science and Technology, 2020)
Background: Cervical cancer is one of the most common malignancy among women in India. By early detection of pre-cancerous lesions & introduction of vaccine, incidence of disease can be reduced. So, it is necessary to assess the awareness among medical students regarding cancer cervix, HPV infection & HPV vaccine. Aim: To study the awareness about cervical cancer, HPV infection and HPV vaccine among medical students. Methods: Cross-sectional study was conducted among 100 undergraduate medical students aged between 18-25 years from III/1 to III/IV during a period of 6 months in Krishna Institute of Medical Sciences, Karad, Maharashtra, based on 25-point questionnaire regarding cancer cervix, HPV infection & HPV vaccine. Results: Among the students,95% were aware of the risk factors for the cervical cancer,38% were aware about screening tests for cervical cancer,89% students answered that cancer cervix is vaccine preventable. Medical students who were not aware about the age group for giving HPV vaccination was 59%. Awareness about male vaccination was present among 73%. None of the medical students were vaccinated. Conclusion: Even though the awareness about cervical cancer & HPV infection is good among medical students, widespread acceptance of HPV vaccine is not present due inadequate knowledge and awareness regarding HPV vaccine. There is a lack of understanding regarding the cost, availability, extent of protection against cervical cancer & safety conferred by the HPV vaccine.